Mediating the sport consumer behaviour model: Analysis in non-sporting brand - Dalangin, Jerico John G.; Pascua, Luigi L; Aquino, Rob Jason; Cereno Jr, Efren P (Faculty of Communications Science, Dr. Soetomo University, 2020)
In the Philippines, sports sponsorship has already found its way, as companies invest in sponsoring a team or creating their brand of league. In volleyball, a pizza chain created an entire volleyball league, even though its products are not connected with sports nor even a healthy option food. This study was conducted in a Philippines private university whose total population was 2,200 during the time of the study. Slovin’s Formula was used to select 338 respondents. Mediation analysis was done to explore the direct and indirect effects between the independent and dependent variables. Regression analysis was also conducted to test the prediction of the latent variables. Based on the result, constructs of sports consumer behaviour (Involvement, Sport Attachment, Brand Image, Word of Mouth, and Purchase Intentions) in sports sponsorship activity could be effective in the Philippine setting. It can be lauded that, sports attachment, brand image, income and educational attainment could profoundly influence word of mouth and purchase intention separately. This means that respondents who have sports attachments, perspectives on brand image, certain educational attainment levels, and middle and upper disposable income can be useful whether they are exposed to the brand as long as the sports sponsor can turn into a brand ambassador who can provide testimonials to the brand or people who can contribute to brand sales.